IMPLEMENTATION "SUBSTANCE OVER FORM" AND "BUSINESS PURPOSE" DOCTRINES IN DOMESTIC RULES OF TRANSFER PRICING - KURILOV, YEVHEN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
At aticle analyzes changes in the domestic tax legislation on the introduction of such interconnected and complementary doctrines of international tax law as "substance over form" and "business purpose". The essence of these doctrines, their relationship with the principles and standards of financial reporting, financial and tax accounting, as well as their likely impact on the domestic transfer pricing rules are considered. The analysis of the existing practice in Ukraine of the application of these doctrines in court cases on tax issues is carried out. The problematic aspects of their application for tax control over the observance of transfer pricing rules by taxpayers have been identified. The practical application of interrelated doctrines of international tax law, such as "substance over form" and "business purpose", provides for the implementation of a set of measures to document and study the subjective component of a separate controlled transaction and the activities of a taxpayer as a whole and / or an international group of companies as a whole (strategies goals, intentions and expectations). The taxpayer must be ready and able to explain in his transfer pricing documentation and/or during audits to the officials of the regulatory body the economic effect obtained from the implementation of the controlled transaction. To this end, the following are essential: in-depth attention to transactions that may be considered risky for transfer pricing; proper justification and documentation of activities related to the implementation of a controlled transaction in all areas and levels of accounting. The conclusion is also formulated that the concept of "business purpose" is evaluative in nature, allowing to predict the further development of practical developments in the field of application of the "business purpose" doctrine in Ukraine, incl. as a result of further jurisprudence.